Observation of the ballooning mode that limits the operation space of the high-density super-dense-core plasma in the LHD. (8th May 2017) - Ohdachi, S.; Watanabe, K.Y.; Tanaka, K.; Suzuki, Y.; Takemura, Y.; Sakakibara, S.; Du, X.D.; Bando, T.; Narushima, Y.; Sakamoto, R.; Miyazawa, J.; Motojima, G.; et al.
Abstract: The central beta of the super-dense-core (SDC) plasma in the large helical device (LHD) is limited by a large scale MHD event called 'core density collapse' (CDC). The detailed measurement reveals that a new type of ballooning mode, quite localized in space and destabilized from the 3D nature of Heliotron devices, is the cause of the CDC. It is the first observation of an unstable mode in a region with global negative magnetic shear. Avoidance of the excitation of this mode is a key to expand the operational limit of the LHD.